The Soviet city and the ‘other cultural’ heritage - Юлия Косенкова (Проект Байкал)
Little is known about the relationship between ‘ours’ and the ‘other’ in Soviet architecture. Attitudes to heritage in the Kaliningrad region and in the former Central Asian republics, despite their dissimilarity, have much in common. The architectural and town-planning heritage, which had been developed in these regions for centuries and reflected the peculiarities of local culture, was perceived as ‘other cultural’, oppositional to the Soviet regime. The article considers the attitude to the ‘other cultural’ heritage in the formation of architectural and spatial environment of Soviet cities.